You can use either the substitution or elimination method. To use substitution, you would solve on of the equations in terms of either x or y, then substitute that expression for the variable in the other equation. For example, using the first equation to solve for x, you would get x = (16 - 3y)/12 = 4/3 - y/4. Then we could substitute this for x in the second equation to solve for y: -36x - 9y = 32-36(4/3 - y/4) - 9y = 32 -48 + 9y - 9y = 32 -48 = 32-48 = 32 is a contradiction, and so, there is no solution. To use the elimination method, we would multiply one or both of the equations by a constant then add the two equations together in an attempt to eliminate one of the variables. For example, if we multiply the first equation by 3, we get: 3(12x + 3y = 16) ----> 36x + 9y = 48And now we'd add this equation with the second to get 36x + 9y = 48-36x - 9y = 32 0 = 80...another contradiction ...no solution.